Analisis Efektivitas Dan Kontribusi Pajak Restoran dan Pajak Hotel Terhadap Pendapatan Asli Daerah Kota Manado Tahun 2021-2023 - Baraguna, Nikki C.; Wangarry, Andreas R.; Pangemanan, Shane A.; Putong, Ivonne H. (Cattleya Darmaya Fortuna, 2025)
The Manado City Regional Revenue Agency (BAPENDA) is a local government agency in Manado City, North Sulawesi Province, Indonesia which is tasked with managing and optimising Manado City's own-source revenue (PAD). The purpose of the study, namely to determine and analyse the calculation and contribution of restaurant tax and hotel tax to Manado City's local revenue in 2021-2023. The research method used is qualitative method. The data sources of this research are primary data and secondary data, data collection techniques through observation, interviews, documentation, literature studies, and the internet, the data analysis used in this research is a qualitative descriptive analysis method, namely analysing, describing, and summarizing the data obtained, namely the target data and the realization of local revenue, local taxes (restaurant tax and hotel tax), in this study researchers used calculation analysis and contribution analysis to obtain relevant and accurate results. The results showed that the effectiveness analysis of restaurant tax from 2021-2023 averaged 105.9% with very effective criteria while hotel tax from 2021-2023 averaged 68% with less effective criteria. Analysis of the contribution of restaurant tax from 2021-2023 averaged 28.97% with moderate criteria and also analysis of hotel tax contributions from 2021-2023 averaged 9.3% with very poor criteria.